Epidemiological and clinical importance of leptospirosis: Bangladesh perspective - Patwary, Md Ismail; Bari, Mohammad Zabed Jillul; Islam, Towhidul (Bangladesh Medical Journal, 2017)
Abstract not available Bangladesh Med J. 2016 Sep; 45 (3): 167-168